Ensuring Digital Accessibility Through Process and Policy - Lazar, Jonathan; Goldstein, Daniel F; Taylor, Anne (Elsevier Science & Technology, 2015)
Ensuring Digital Accessibility through Process and Policy provides readers with a must-have resource to digital accessibility from both a technical and policy perspective. Inaccessible digital interfaces and content often lead to forms of societal discrimination that may be illegal under various laws. This book is unique in that it provides a multi-disciplinary understanding of digital accessibility. The book discusses the history of accessible computing, an understanding of why digital accessibility is socially and legally important, and provides both technical details (interface standards, evaluation methods) and legal details (laws, lawsuits, and regulations). The book provides real-world examples throughout, highlighting organizations that are doing an effective job with providing equal access to digital information for people with disabilities. This isn’t a book strictly about interface design, nor is it a book strictly about law. For people who are charged with implementing accessible technology and content, this book will serve as a one-stop guide to understanding digital accessibility, offering an overview of current laws, regulations, technical standards, evaluation techniques, as well as best practices and suggestions for implementing solutions and monitoring for compliance. This combination of skills from the three authors—law, technical, and research, with experience in both corporate, government, and educational settings, is unique to this book, and does not exist in any other book about any aspect of IT accessibility. The authors’ combination of skills marks a unique and valuable perspective, and provides insider knowledge on current best practices, corporate policies, and technical instructions. Together, we can ensure that the world of digital information is open to all users.Learn about the societal and organizational benefits of making information technology accessible for people with disabilitiesUnderstand the interface guidelines, accessibility evaluation methods, and compliance monitoring techniques, needed to ensure accessible content and technologyUnderstand the various laws and regulations that require accessible technologyLearn from case studies of organizations that are successfully implementing accessibility in their technologies and digital content